The Influence of Product Quality and Promotion on Repurchase Pertamax through Consumer Satisfaction in Makassar City - Irfan Saputra; Osman Lewangka; Abdul Razak Munir (Magister Management, Hasanuddin University, 2020)
Pertamax is a non-subsidized fuel PT. Pertamina (Persero) and the company's biggest challenge is to change the buying pattern of people in order to switch from Premium to Pertamax. To change the buying pattern of a company's society should look at consumer behavior as well as the attributes contained in the product in order to provide satisfaction and re-purchase decisions. These attributes are product quality and promotion. This research aims to determine the quality of products and promotions positively and significantly affect consumer satisfaction, knowing product quality, promotion, and customer satisfaction positively and significantly towards purchasing decisions, and product quality and promotions have a positive and significant effect on the re-purchase decision through consumer satisfaction of Pertamax in the Makassar city. The population in this study was the consumer of Pertamax in the town of Makassar, which was designated 100 samples of respondents. Data collection techniques through questionnaires, literature, and observation studies, using path analysis techniques. The results of the product quality are positive and significant to customer satisfaction. Promotions have a positive and insignificant impact on consumer satisfaction. Consumer satisfaction has a positive and significant effect on repurchase decisions. The quality of products directly has a positive and significant effect on repurchase decisions. Directly promotion is positive and insignificant to repurchase decisions. The quality of products indirectly through consumer satisfaction has a positive and significant influence over the repurchase decision. Indirectly promotion through consumer satisfaction had a positive but insignificant influence on the repurchase decision of Pertamax in Makassar city.